Fiber Reinforced Cementitious Matrix (FRCM) for strengthening historical stone masonry structures: Experiments and computations. (1st December 2020) - Angiolilli, Michele; Gregori, Amedeo; Pathirage, Madura; Cusatis, Gianluca
Highlights: Diagonal compression tests and numerical simulations of stone masonry. LDPM allows to reproduce the mechanical behavior and damage evolution of stone masonry. The thickness of the mortar layer of FRCMs govern the strength of reinforced samples. The bond behavior at the mortar-masonry interface highly influences the ductility of reinforced samples. The fiber grid influences only the ductility of the reinforced samples and has no effect on the strength. Abstract: Seismic events highlight the inherent fragility and vulnerability of stone masonry buildings, which represent a large part of the existing historical and artistic heritage. In order to preserve these structures, numerous reinforcement techniques are typically used on masonry walls, including mortar injections, reinforced drilling, and reinforced concrete plaster. Nowadays new and less invasive strengthening techniques are preferred; among them Fiber Reinforced Cementitious Matrix (FRCM) system with lime-based mortar, which is considered to be more compatible with the intrinsic properties of these ancient structures as compared to cement-based mortar. This work aims to investigate experimentally and computationally FRCM applied as reinforcement to ancient stone masonry. In particular, the paper presents results from diagonal compression tests carried out at the University of L'Aquila (Italy) on stone masonry specimens strengthened with layers of Glass-FRCM (GFRCM). In comparison with unreinforced panels, those strengthened by the GFRCM exhibited a significant increase in shear modulus and shear strength. A computational framework based on the Lattice Discrete Particle Model (LDPM) was then used to reproduce the experimental results. The fracture behavior and the damage evolution in masonry panels were investigated under different assumptions on the GFRCM system features (bond behavior, mortar thickness, fiber anchors and fiber grid). The good agreement between experimental results and the LDPM simulations show that this approach predicts well the mechanical behavior and the damage evolution in stone masonry under quasi-static loading conditions. Moreover, it can be considered a viable tool for engineers in developing effective reinforcement techniques.